Litterfall seasonality and adaptive strategies of tropical and subtropical evergreen forests in China. (27th August 2021) - Dai, Yuhang; Gong, Fanxi; Yang, Xueqin; Chen, Xiuzhi; Su, Yongxian; Liu, Liyang; Wu, Jianping; Liu, Xiaodong; Sun, Qingling
Abstract: Tropical and subtropical evergreen broad-leaved forests (EBFs) and needle-leaved forests (ENFs) in China exhibit complex leaf shedding strategies in responses to soil water availability, vapor pressure deficits (VPDs) and sunlight availability. However, the seasonal variations and triggers of litterfall differ significantly in tropical/subtropical forests, and there are still many uncertainties. Herein, we aim to explore the distinct climatic factors of seasonal litterfall in a climate–phenology correlation framework. We collected seasonal litterfall data from 85 sites across tropical/subtropical China and used linear correlation coefficients between sunlight and rainfall to partition synchronous/asynchronous climates. Additional phase analysis and structural equation model analysis were conducted to model the climatic triggers of tropical phenology. Results indicated two types of tropical litterfall phenology under two types of climates. In synchronous climates, where seasonal sunlight and rainfall are positively correlated, the litterfall peak of the unimodal phenology and the first litterfall peak of the bimodal phenology both happen at the end of dry season. The second litterfall peak of the bimodal phenology occurs at the end of rainy season due to water stress. In asynchronous climates, where seasonal sunlight and rainfall are negatively correlated, VPD shows consistent seasonal variations with incoming sunlight. The leaf senescence is accelerated at the end of dry season by higher VPD; while soil water deficit is in anti-phase with sunlight and mainly controls the second litterfall peak of the bimodal phenology in EBF. Our findings provide an important reference for modeling tropical phenology in Earth system models.